Pengaruh Promosi Digital dan Brand Image Terhadap Keputusan Pembelian Konsumen di Kopi Kenangan Jatijajar Depok - Dhea Agustina; Lady Diana Warpindyastuti; Dwi Puji Hestuti (Indo Publishing, 2026)
The increasingly intense competition among coffee shop businesses encourages companies to implement effective marketing strategies to attract consumers and remain competitive in the market. This study aims to examine the influence of Digital Promotion (X1) and Brand Image (X2) on Purchase Decision (Y) among consumers at Kopi Kenangan Jatijajar, Depok. This research employed a quantitative method by distributing questionnaires to consumers of Kopi Kenangan Jatijajar, Depok. The sampling technique used was purposive sampling, with a total sample of 97 respondents. The data were analyzed using multiple linear regression analysis with the assistance of SPSS version 26. The results indicate that Digital Promotion (X1) and Brand Image (X2) each have a positive and significant effect on Purchase Decision (Y). Digital Promotion (X1) contributes 53.6% to Purchase Decision, while Brand Image (X2) contributes 25.6%. Simultaneously, Digital Promotion (X1) and Brand Image (X2) also have a significant effect on Purchase Decision (Y), with a combined contribution of 79.2%, while the remaining 20.8% is influenced by other external factors.